PEMBANGKITAN TENAGA LISTRIK PULAU JAWA DALAM UPAYA PENGURANGAN EMISI CO2 - Muhamad Muchlis (Jurnal Energi dan Lingkungan (Enerlink), 2005)
Green house gases such as CO2, CH4, N2O emissions have contributed to the global warming that would lead to increase on sea level, and acid rain. However, CO2 has most contribution to the impact. Most of the green house gases emission in the atmosphere is released from fossil energy in transportation sector, power generation sector, industrial sector and household sector. Therefore, reducing the greenhouse gases from energy utilization especially in power generation sector is more controllable in the energy utilization.Kata kunci:Â CO2, PLTU, emisi, tenaga listrik.